2015
DOI: 10.1007/s00417-015-3102-3
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy ab interno with the Trabectome® as a therapeutic option for uveitic secondary glaucoma

Abstract: Trabeculectomy ab interno with the Trabectome® is a minimally invasive and effective method for controlling IOP in uveitic secondary glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
5
18
3
4
Order By: Relevance
“…12 This study found similar results to ours, patients presented with elevated IOP at presentation 31 ± 6.7 mmHg and had a 40% lowering of IOP on average. 12 This study found similar results to ours, patients presented with elevated IOP at presentation 31 ± 6.7 mmHg and had a 40% lowering of IOP on average.…”
Section: Discussionsupporting
confidence: 91%
“…12 This study found similar results to ours, patients presented with elevated IOP at presentation 31 ± 6.7 mmHg and had a 40% lowering of IOP on average. 12 This study found similar results to ours, patients presented with elevated IOP at presentation 31 ± 6.7 mmHg and had a 40% lowering of IOP on average.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, these serious complications have not been reported after XEN‐45 implantation in eyes with primary open angle glaucoma . In comparison, ab interno trabeculectomy with the Trabectome was found to be effective for the treatment of uveitic glaucoma but was not associated with persistent hypotony or ocular infections . In our study, there was a high rate of transient postoperative hypotony associated with a shallow anterior chamber, with approximately 20% of patients requiring anterior chamber reformation with viscoelastic.…”
Section: Discussionmentioning
confidence: 51%
“…It is one of the most difficult forms of glaucoma to manage, because the ophthalmologist must simultaneously address inflammation and elevated IOP. Among the current surgical treatment options are trabeculectomy, deep sclerectomy, minimally invasive glaucoma surgery (MIGS; e.g., trabectome), cyclodestructive procedures, and several types of glaucoma drainage devices (GDD), with comparable efficacy [57]. However, the long-term role of trabeculectomy in patients with uveitis is compromised by young age, inflammation-induced fibrosis and conjunctival scarring, and scleral thinning, making trabeculectomy in many cases not the optimal choice.…”
Section: Introductionmentioning
confidence: 99%